Dental pathology of the wild Iberian wolf (Canis lupus signatus): The study of a 20(th) century Portuguese museum collection - Pires, AE (Vet Anim Sci, 2020)
For some wild canids, such as the Iberian wolf, there is a lack of in-depth knowledge about dental pathology. We aimed to evaluate it, in a standardized manner, in specimens from a Portuguese museum collection. Sixty-five deceased specimens of wild Iberian wolves, 61 complete skulls and 4 mandibles, collected in Portugal between 1977 and 1995, were analyzed. Sample comprised 18 females, 24 males and 23 individuals of undetermined sex. Teeth were evaluated by visual observation and dental radiography for tooth wear, periodontitis, fractures and other dental lesions. We have found several causes for teeth absence: artefactual, secondary to periodontitis and agenesia. About 30% of the teeth showed signs of wear. Only a small (<13%) fraction of maxillary and mandibular teeth did not show periodontitis. The tooth 308 showed periodontitis in all males (p = 0.017) and the tooth 104 was significantly affected by this condition in females (p = 0.020). A significant relationship was found between females and tooth wear in three teeth. Periodontitis showed a significant association with tooth wear (p < 0.001) and fractures (p = 0.027). Tooth fractures were more frequent in the maxilla than in the mandible. Seven periapical lesions, seven root fusions and three specimens with malocclusion were identified in the collection. Results are discussed integrating information from diet, habitat, genetic and spatial behavior. Dental radiography is here proposed as an approach for the age estimation in archaeological canids. This research contributes to the knowledge of the dental disease in the largest wolf population in Western Europe, a target subspecies of multiple conservation measures.